2021
DOI: 10.4018/ijrdis.20210101.oa2
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Innovation for Competitive Advantage in Large Firms and SMEs

Abstract: The aim of this study is to empirically investigate how transformational leadership (TL) practices encourage innovation for competitive advantage within the specific context of Saudi large firms and SMEs. Despite a profusion of studies noting that innovation strongly contributes to a firm’s performance, there is a dearth of studies about how TL practically encourages organizational innovativeness. Moreover, because many leadership studies are limited in their location to Western nations, further research in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The stylized facts known about SME performance may be reflected in a picture of SME competitiveness generated by organizing around the three main pillars of SME competitiveness previously mentioned [2]. Studies in [3] show that SMEs are less competitive than large businesses, and that this disparity is much worse in emerging nations than in industrialized ones. By focusing on competitiveness indicators rather than productivity data, it is possible to understand the factors that contribute to differences in competitiveness, which is vital information for decision makers and investment and trade support organizations that want to facilitate the internationalization of SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…The stylized facts known about SME performance may be reflected in a picture of SME competitiveness generated by organizing around the three main pillars of SME competitiveness previously mentioned [2]. Studies in [3] show that SMEs are less competitive than large businesses, and that this disparity is much worse in emerging nations than in industrialized ones. By focusing on competitiveness indicators rather than productivity data, it is possible to understand the factors that contribute to differences in competitiveness, which is vital information for decision makers and investment and trade support organizations that want to facilitate the internationalization of SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical studies have found that the competitiveness of MSMEs is influenced by many factors, especially in Aceh Province, especially during the current Covid 19 Pandemic, among the factors that cause the low competitiveness of MSMEs is the lack of guidance for MSME actors. (Dixon & Pusparini, 2020;Susana, Darsono, & Andarwati, 2020), product innovation (Ashoor, 2021;Christa & Kristinae, 2021;Sulistyo & Ayuni, 2020), access to capital (Abbas, 2018;Munifatik, Askandar, & Mahsuni, 2018), marketing orientation (Ali, Hilman, & Gorondutse, 2020;Puspaningrum, 2020;Rajadurai, Zahari, Esa, Bathmanathan, & Isaac, 2021). The novelty of this advanced research lies in the selection of methods and processes for designing a model to increase the competitiveness of Micro, Small and Medium Enterprises through a review of capital, product innovation and marketing orientation.…”
Section: Introductionmentioning
confidence: 99%